Filmic deconstruction: Three tools for audio-visual analysis in arts-based research - Torres-Carceller, Andrés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Arts-based research is a methodological approach that questions rational and objective scientism as the only valid means of enquiry, developing a corpus of procedures linked to the arts whose main objective is not so much to provide evidence, but to offer new perspectives by incorporating artistic disciplines as a means of investigation. The compositional features of five audio-visual creations are analysed on the basis of deconstruction by studying their visual configuration in frames and filmic rhythm, using two instruments of quantitative visual analysis and visual averages.